The Periodic Solutions for Planar -Body Problems - Xiaohong Hu; Changrong Zhu (Abstract and Applied Analysis)
Based on the works of Perko and Walter, Moeckel and Simo, and Zhang and Zhou, we study the necessary conditions and suffcient conditions for the uniformly rotating planar nested regular polygonal periodic solutions for the -body problems.